What Coaches Believe are Best Practices for Coaching: A Qualitative Study of Interviews from Coaches Residing in Asia and Europe. Issue 2 (22nd August 2013) - Gentry, William A.; Manning, Lisa; Wolf, Ali Kyle; Hernez‐Broome, Gina; Allen, Leigh Whittier
Abstract The industry of executive and leadership coaching has grown over the past decade, becoming an integral part of many leadership and executive training and development initiatives globally. As a result, research focusing on coaches in Asia and Europe may uncover useful best practices that could inform the field. Such knowledge would enable coaches to better understand how to work better with their client–leaders and can also inform and develop coaching practice and research. The purpose of our qualitative study was to understand, through the interviews of 12 practicing coaches residing in Asia and 19 practicing coaches residing in Europe, what their best practices are in one‐to‐one coaching engagements. Ten best practices from the coaches in Asia and six best practices from the coaches in Europe emerged. Each best practice is discussed as well as limitations, future research, and implications from the findings of our study.